1996
DOI: 10.1590/s0037-86821996000500008
|View full text |Cite
|
Sign up to set email alerts
|

Efeito de Momordica charantia I. Em camundongos infectados por Plasmodium berghei

Abstract: According to the World Health Organization malaria is one of the major public health problems in Brazil and all over developing countries, where 80% of the population use traditional medicine to solve their primary medical problems. Both treatment and control of this parasitosis have become difficult, because of parasite strains that are resistant to conventional drugs, such as chloroquine. That makes the search for new antimalarial drugs not only important but urgent. We aimed therefore at evaluating the effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
1

Year Published

2004
2004
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 19 publications
0
7
0
1
Order By: Relevance
“…Except Alchornea cordifolia leaves, Momordica charantia whole plant and Plumbago zeylanica for which some antiprotozoal activities were previously reported (Amorin et al, 1991;Ueno et al, 1996;Marshall et al, 2000;Muňoz et al, 2000;Simonsen et al, 2001;Banzouzi et al, 2002;Okpekon et al, 2004), this is the first report of the antiprotozoal activity of the remaining ethnobotanically selected medicinal plants.…”
Section: Resultsmentioning
confidence: 68%
“…Except Alchornea cordifolia leaves, Momordica charantia whole plant and Plumbago zeylanica for which some antiprotozoal activities were previously reported (Amorin et al, 1991;Ueno et al, 1996;Marshall et al, 2000;Muňoz et al, 2000;Simonsen et al, 2001;Banzouzi et al, 2002;Okpekon et al, 2004), this is the first report of the antiprotozoal activity of the remaining ethnobotanically selected medicinal plants.…”
Section: Resultsmentioning
confidence: 68%
“…Munoz et al (2000) demonstrated moderate in vivo activity of MC extract against rodent malaria P. vinckei petteri 279. However, Amorim et al (1991) and Ueno et al (1996) did not observe in vitro antiplasmodial activity of ethanolic MC extract against P. berghei.…”
Section: Anthelmintic Studymentioning
confidence: 69%
“…So the 95% ethanol extract obtained from the dried seed of Cucurbita maxima popularly known as pumpkin strawberries was active in dose of 250 mg/kg against P. berghei infected mice (Amorim et al, 1991) and Momordica charantia, called as melon from São Caetano, had the aqueous and chloroform extracts obtained of the dried flowers or aerial parts inactive against P. berghei, P. gallinaceum, P. cathemerium and P. lophurae (Carvalho et al, 1991;Spencer et al, 1947), the 95% ethanol extract obtained Ingrid R. Mariath, Heloina de S. Falcão, José M. Barbosa-Filho, et al of the dried leaves in the dose of 500 mg/kg was also inactive against P. berghei infected mice (Amorim et al, 1991), while the infusion and 95% ethanol extract of the dried leaves and stem in dose of 1.0 g/kg were active against P. berghei infected human or mice (Ueno et al, 1996).…”
Section: Resultsmentioning
confidence: 99%